PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA KOMIK TERHADAP KEMAMPUAN BERPIKIR KRITIS DANHASIL BELAJAR PESERTA DIDIK KELAS V PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI SEKOLAH DASAR GUGUS III KEC. RAPPOCINI - Haula Wahdania; Andi Sugiati; Abdul Azis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the effect of using the Problem Based Learning Model on the critical thinking skills and learning outcomes of class V students in the Pancasila Education subject at Cluster III Elementary School, Rappocini District. This type of research is quantitative research with a quasi-experimental or quasi-experimental method. The research design used was a pretest-posttest non-equivalent control group design. The population in the study was all class V students in elementary school cluster III, Rappocini District, totaling 240 students. The research sample consisted of 60 students who were divided into two class groups, namely the experimental class and the control class and were selected using a simple random sampling technique. The data collection techniques used are observation, tests and documentation. Data analysis techniques use descriptive analysis techniques and inferential analysis techniques. The results of this research found that the critical thinking skills and learning outcomes of students using the Problem Based Learning Model assisted by comic media obtained an average pretest score of 51.17 and an average posttest score of 83.67. So it can be concluded that the critical thinking skills and learning outcomes of students using the comic-assisted PBL model are better than before treatment. Meanwhile, critical thinking skills and learning outcomes using conventional models in the control class obtained an average pretest score of 54.81 and an average posttest score of 80.33. From the hypothesis test, a sig (2-tailed) value of 0.000 is obtained, which is smaller than 0.05, so it is concluded that H0 is rejected and H1 is accepted, meaning that there is a positive and significant influence of the use of the Problem Based Learning Model on students' critical thinking abilities.